The Performance of Tall Timber Buildings under Lateral Loads - Arnebrant,Erik (TVBK-5000, 2024)
Pollution and its impact on the environment is one of the greatest problems facing humanity today. Since the building sector is responsible for 40% of the total carbon dioxide emissions, it is important to investigate the sector to see how emissions can be reduced. Due to timber having a smaller impact on the environment compared to steel and concrete, it is of substance to investigate the possibilities of building with timber. High-rise buildings are characterized by being built of steel and concrete, although there are some medium high-rise buildings made out of timber. As a material, timber is lighter and more flexible than steel and concrete which makes timber more prone to deflect due to loads. Therefore, it can be hard to meet the requirements for the serviceability-limit state when designing lateral stabilizing systems out of timber. On top of that, the connections between timber elements are also prone to deflect (slip) when affected by loads. To simulate the timber connections behavior, the connections are usually modeled with a low-stiffness spring. The purpose of this thesis was to compare the behavior of several lateral stabilizing systems under static and dynamic loads. This was carried out in terms of static deflections and modal parameters. The thesis consists of a background on the static- and dynamic behavior of high-rise buildings, timber as a building material, and a case study regarding the medium-rise building ”Mjøstårnet” located in Norway. The original structure is made out of glulam and is stabilized by truss-systems in the facade but alternative stabilizing systems are also investigated. The results of static and dynamic behavior concerning wind load (both winds along the long- and short facade) showed that both design alternatives are valid regarding the deflection limit according to Eurocode. However, the modal analysis showed differences between the models, which could be of importance for the dynamic response.
Keywords: Timber; High-rise buildings; Dynamics; FEM; Modal Analysis; Wind Load